derive x/(1-x^2) - Wolfram|Alpha How on earth does 1-x^2 become x^2-1?! Thanks.
Follow Math Help Forum on Facebook and Google+
$\displaystyle (1-x^2)^2 = x^4 - 2x^2 + 1 $ $\displaystyle (x^2-1)^2 = x^4 - 2x^2 + 1 $ This is because, for square functions f(-x) = f(x)
Last edited by jakncoke; Feb 24th 2013 at 04:45 PM.
Originally Posted by jakncoke $\displaystyle (1-x^2)^2 = x^4 - 2x^2 + 1 $ $\displaystyle (x^2-1)^2 = x^4 - 2x^2 + 1 $ Doh..I did suspect that, but I dismissed it as being too far out. Why go through the step of re-arranging it. Weird calculator.
View Tag Cloud